Secular trend in height in enlisted men and recruits from the Brazilian Navy born from 1970 to 1977 - Kac Gilberto; Santos Ricardo Ventura (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1997)
This study presents data from a survey on height trends in Brazilian Navy enlisted men and recruits born from 1970 to 1977. The sample consisted of 52,574 enlisted men and 4,459 recruits ranging in age from 18.00 to 18.99 years. The statistical processing employed two-way analysis of variance procedure, simple linear regression comparing height and year of birth and multiple analysis controlling for schooling (regression coefficient) and the chi-square. The results show that enlisted men and recruits displayed height increments, characterizing a contemporary process of secular trend. Such increments were also present in the country's various macro-regions. The results were compared to a recent investigation of a national scope the National Survey on Health and Nutrition (PNSN) and both enlisted men and recruits displayed higher median height than that reported by the PNSN. Level of schooling for individuals in the Navy is high, far superior to that of the Brazilian population as a whole. This set of data suggests that young men enlisting in the Navy are on average of a higher socioeconomic status than the Brazilian population in general, which limits possibilities for extrapolating the findings from this research.